The Effect Of Good Corporate Governance, Return On Assets (ROA), And Debt Ratio (DER) On Company Value In The Banking Sub-Sector Listed On The IDX For The 2016 – 2020 Period - alem ivana; Windi Novianti (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2022)
The purpose of this research is to determine good corporate governance, return on asset, and debt to equity ratio and to find the influence of GCG, ROA, and DER on company value partially or simultaneously. The method used is descriptive and verificative method. Data is collected through data processing that already exists in the news, and the official website. The statistical tests used are classical assumptions, path regression analysis, correlation coefficient analysis, coefficient of determination and hypothesis testing using the T Test (partial) and F Test (simultaneous). The results of descriptive research show that goodcorporate governance, return on asset, and debt to equityratio in the banking sub-sector are considered positive. While the results of the research show that good corporate governance has an effect on the value of the company, the rate of return on assets has an effect on the value of the company, the debt to equity ratio has an effect on the value of the company. Good corporate governance, Level of Return on Assets, Debt to Equity Ratio has an influence on Company Value in Banking Sub-Sector Companies Registered in BEI.